AKOMODASI BUDAYA LOKAL DALAM LEGISLASI HUKUM KELUARGA DI INDONESIA - M Samson Fajar; Sabdo Sabdo (IAIN Manado, 2018)
Abstract: Culture as a result of the free and dual human creative power of the natural world, it encompasses the material matters (Immaterial) and Maddi (material), real and unreal objects, Malmusah and Ghairu malmusah (palpable and untouched). Essentially, culture (Tsaqafah) is expressed as the product of human reason consisting of patterns, steady attitudes, thoughts, feelings, and reactions obtained and is primarily derived by symbols that make up its achievement independently of human groups. The nature of this Islamic responsiveness has been built by the Prophet (s) when prohibiting Khamr, forbidding the worship of idols and other shari'ah. How Rasulullah saw is very careful and gradual in doing da'wah, so achieved the success of da'wah in upholding Islamic creed and shari'ah at that time. Today many problems in the establishment of law and legislation, legislators are more concerned with intellectual subjectivity and importance than the objectivity of humanity to the benefit, resulting in policies that are not responsive to the needs of society. The author in this context tries to inventory the various local wisdom of the Muslim community in the archipelago that is relevant as an approach in establishing legislation based on local culture.Keywords: Local Culture, Legislation, Islamic Law Abstrak. Budaya merupakan hasil dari kreativitas manusiawi yang bebas dan alamiah, meliputi sisi immaterial dan materi, objek nyata dan tidak nyata, malmusah dan ghairu malmusah (gamblang dan tak tersentuh). Pada dasarnya, budaya (tsaqafah) merupakan produk akal manusia yang terdiri dari pola, kesantunan, pikiran, perasaan, dan reaksi yang diperoleh dan terutama berasal oleh simbol yang membentuk pencapaiannya secara mandiri dari kelompok manusia. Sifat dari respon Islam ini telah dibangun oleh Nabi (s) ketika melarang khamr, melarang penyembahan berhala dan syariah lainnya. Bagaimana Rasulullah melihat sangat hati-hati dan bertahap dalam melakukan dakwah, sehingga mencapai keberhasilan dakwah dalam menegakkan akidah Islam dan syari'ah pada waktu itu. Saat ini banyak masalah dalam pembentukan hukum dan undang-undang, di mana legislator lebih peduli dengan kepentingan subjektivitas intelektual daripada kepentingan objektivitas kemanusiaan, sehingga kebijakan yang lahir tidak responsif terhadap kebutuhan masyarakat. Penulis dalam konteks ini mencoba untuk menginventarisasi berbagai kearifan lokal komunitas Muslim di nusantara yang relevan sebagai pendekatan dalam menetapkan perundang-undangan berdasarkan budaya lokal.Kata Kunci: Budaya Lokal, Legislasi, Hukum Islam